2021
DOI: 10.3390/app11041815
|View full text |Cite
|
Sign up to set email alerts
|

Modification of PLA Scaffold Surface for Medical Applications

Abstract: Materials used for medical applications (e.g., the cellular scaffold) should have not only the specific chemical composition, but the surface layer properties as well. For this reason, a method which enables an increase in the number of pores, wettability of the surface, and improvement the conditions of nutrient transportation into the membrane is being studied. The plasma of a dielectric barrier discharge was applied for the surface modification of polylactide obtained by dry or wet phase inversion. The plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…However, these results remained consistent with the findings from XPS and FTIR that showed the formation of new oxygen-bearing functional groups. The presented contact angles for both the pristine and plasma-treated PLA-T and PLA-MC corresponded to those reported in the literature [36][37][38], as did the observed increase in SFE from 47.9 and 45.8 mJ/m 2 , respectively, to 61.0 and 61.2 mJ/m 2 [30,39]. It must be also noticed that changes induced by plasma are prone to disappear with time [26,37].…”
Section: Contact Angle and Surface Free Energy (Sfe)supporting
confidence: 87%
“…However, these results remained consistent with the findings from XPS and FTIR that showed the formation of new oxygen-bearing functional groups. The presented contact angles for both the pristine and plasma-treated PLA-T and PLA-MC corresponded to those reported in the literature [36][37][38], as did the observed increase in SFE from 47.9 and 45.8 mJ/m 2 , respectively, to 61.0 and 61.2 mJ/m 2 [30,39]. It must be also noticed that changes induced by plasma are prone to disappear with time [26,37].…”
Section: Contact Angle and Surface Free Energy (Sfe)supporting
confidence: 87%
“…It is essential to confirm that the material is safe for the body and does not cause adverse acute or long-term reactions. Similar requirements are placed on various other implants, not only artificial cellular scaffolds [ 395 , 396 , 397 , 398 , 399 , 400 , 401 , 402 ].…”
Section: Artificial Substitutes Of the Extracellular Matrixmentioning
confidence: 88%
“…PLA hydrophobicity renders bone cell attachment and proliferation difficult [35]. It has been reported that to enhance the surface of an IPTS cell chip, a surface modification method using a material capable of increasing the surface adhesive force, wettability, roughness, and the number of built-in functional groups must be considered [36]. Some studies reported increased cell proliferation after surface roughening [7], surface modification by peptides, hyaluronic acid incubation, addition of collagen, and mussel adhesive proteins [37].…”
Section: Properties Of the Ipts Cell Chipmentioning
confidence: 99%